Agricultural biotechnology for poverty alleviation: one more arrow in the quiver! - Seré Rabé, Carlos; Rege, J.E.O. (Tanzania Society for Animal Production, 2006)
Agriculture is the largest contributor to the economies of many African countries, generating more than half of the annual Gross Domestic Product (GDP) for many of these countries. The livelihoods of most rural and low-income communities in these countries are to a large extent based on agriculture. While global availability of food has increased, 35% of the 800 million poor of the world live in Africa, and face food insecurity. And yet agriculture constitutes, for the majority of these poor, the primary means of survival and livelihood sustenance. Agricultural biotechnology, which comprises a wide range of biological disciplines, offers enormous potential to speed up the development of plant varieties with pro-poor traits such as drought tolerance, pest resistance or tolerance, higher yields, increased nutritional value, among others. Similarly in animal production there is substantial opportunity for development of vaccines and diagnostics targeting diseases which constrain livestock production in developing regions of the world. In addition, genetic markers can aid breeding of livestock for important traits such as disease resistance, improved product quality as well as improved productivity. However, to date, the innovation essential to achieve these improvements has largely remained a technology of the North. While biotechnology does not provide the ‘silver bullet’ for poverty alleviation, it does enhance the effectiveness of other disciplines such as plant breeding, integrated pest and nutrient management, and livestock breeding, feeding and disease management. Importantly, because use of these technologies, as any other, is associated with risks, African scientists need to have access to the knowledge and scientific infrastructure to assess these risks and to contribute to better informed public discussions of the opportunities and challenges of these technologies. Should biotechnology be a preserve for the rich? Can developing nations afford to ignore the potential of biotechnology? Rather than debate on whether biotechnology can meet the needs of the poor, this paper argues that being just one aspect of a complex set of inter-related interventions required to enhance the contribution of agricultural development to poverty alleviation, discussions should be had on how best to take advantage of the opportunities and manage the risks associated with these technologies, for the benefit of the poor. There is need to explore new ways to build the capacity of the public sector - notably national governments in developing countries and development partners, as well as to tap into the resources of the private sector - to enable the continent come up with African solutions to the problem of poverty alleviation. This will require closer collaboration and transfer, between the North and the South, of appropriate biotechnology and the management of bio-safety issues. Thus, risk assessment has to be an integral part of biotechnology research and development. Africa missed out on the ‘Green revolution’, and should not miss out on the ‘Gene revolution’ as well.